Learning Mathematics Through the Modern Didactic Principle of Polyformity - Nikolić, Sanja; Hilčenko, Slavoljub (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Modern teaching of mathematics tries to eliminate the mechanical memorization of a large amount of knowledge, and also tends to avoid the formal development of students’ psychological abilities. It is normal that such teaching implies the development of student abilities, not on worthless mathematical material, but on content that is of high quality in terms of education and training. Solving problems, which arouses students’ interest and triggers ingenuity, producing experiences of the tension of self-engagement, as a result, necessarily has the triumph of the inventor. Such experiences can create a tendency for mental work, making an indelible mark on the spirit and character of a young person.
Keywords: goal of learning mathematics; didactic principle of polyformity; teacher’s role